Clinical autonomy and contractual space - Cash, Keith (Nursing philosophy, 2001)
This paper investigates the idea of clinical autonomy. Whilst there is a considerable literature on moral autonomy there is very little on clinical autonomy except as a sociological phenomenon. Using the results of interviews with Community Psychiatric Nurses in England, the three main theories that they have about clinical autonomy are examined. It is argued that there are substantial problems with these theories and an alternative way of understanding clinical autonomy is proposed, the idea of contractual space.